2017
DOI: 10.1017/s0266462317000782
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Potentially Inappropriate Prescribing for Older People in Primary Care: Cost-Effectiveness of the Opti-Script Intervention

Abstract: Objectives: This study examines the cost-effectiveness of the OPTI-SCRIPT intervention on potentially inappropriate prescribing in primary care.Methods: Economic evaluation, using incremental cost-effectiveness and cost utility analyses, conducted alongside a cluster randomized controlled trial of twenty-one general practices and 196 patients, to compare a multifaceted intervention with usual practice in primary care in Ireland. Potentially inappropriate prescriptions (PIPs) were determined by a pharmacist. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 22 publications
(54 reference statements)
0
35
0
1
Order By: Relevance
“…Currently, prescribing optimisation interventions are primarily focused on older adults, and aim to increase awareness of PIP and improve prescribing appropriateness. 26 , 27 Given the common nature of PIP in middle-aged adults, future research should investigate the benefit of primary care-based interventions to improve prescribing in this group also. For example, clinical decision support (CDS) tools could incorporate the PROMPT criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, prescribing optimisation interventions are primarily focused on older adults, and aim to increase awareness of PIP and improve prescribing appropriateness. 26 , 27 Given the common nature of PIP in middle-aged adults, future research should investigate the benefit of primary care-based interventions to improve prescribing in this group also. For example, clinical decision support (CDS) tools could incorporate the PROMPT criteria.…”
Section: Discussionmentioning
confidence: 99%
“…All-cause mortality was reported in 6 trials (n = 121,314). 18,[21][22][23][24]30,40,53 None of the trials reported a difference between the intervention and control groups, and the data were not suitable for pooling due to heterogeneity of study interventions. Overall, educational interventions probably had no effect on all-cause mortality (moderate certainty).…”
Section: Educational Interventionsmentioning
confidence: 99%
“…Subsequent to the completion of the OPTI-SCRIPT process and economic evaluations, 12 , 13 our research group began formulating the protocol for the definitive trial. In the interim, the Data-driven Quality Improvement in Primary Care (DQIP) trial was published that assessed the effectiveness of a similar intervention that alerted GPs to PIP to facilitate a subsequent medication review, the results of which led our group to re-consider the original research question.…”
Section: Resultsmentioning
confidence: 99%
“… 5 The trial’s parallel mixed methods process evaluation concluded that the intervention was both feasible and acceptable to GPs and patients, however GPs remarked that current practice workload made dedicated medication reviews for all older people unfeasible and that an intervention that focused on more high risk, or as they perceived clinically relevant PIP may be more amenable to incorporating into day to day practice. 12 The economic evaluation concluded that despite being effective there was uncertainty about the cost effectiveness of the intervention, 13 which may have reflected the fact that improved prescribing of proton pump inhibitors may not significantly affect self-rated health status. The DQIP study, a step wedged cluster RCT involving 34 general practices and 33,334 patients, demonstrated that an intervention comprising informatics that alerted GPs to PIP, did improve prescribing and was associated with reduced hospital admissions relating to heart failure and GI bleeding.…”
Section: Resultsmentioning
confidence: 99%